Perception among the Employees of Bank towards the Bancassurance in Nepal - Joshi, Urmila (Nepalese Journal of Insurance and Social Security, 2019)
The study aims to explore the perception of employees working in banking industry and investigates the problems and prospects of bancassurance in Nepal. Quantitative data have been collected from 100 employees working in 20 commercial banks using structured questionnaire. Product design, customer awareness, brand name, distribution channel and awareness of retail banks are considered as independent variables whereas present status of bancassurance is taken as dependent variable in the study. Both descriptive and inferential statistical tools have been applied to analyse the data. The result reveals that there is a positive relation between product design and brand name with present status of bancassurance in Nepal. This means that better the products lead to success of Bancassurance. The results also reveal negative relationship between present status of Bancassurance and consumer awareness, awareness of retail banks and distribution channel. The study concludes that product design and brand name are the major factors affecting current bancassurance status whereas consumer awareness, awareness of retail banks and distribution channel do not affect on current status of bancassurance.